The GABA Receptors - Enna, Salvatore J.; Möhler, Hanns (The Receptors, 2007)
This volume is the third edition of a monograph series that was first published in 1983. The demand for this work is a testament to the impact of studies on -aminobutyric acid (GABA) receptors on the basic understanding of synaptic transmission and on defining the clinical importance of the neurotransmitter system. Chronicled in The GABA Receptors, Third Edition, are the advances made in understanding the molecular and pharmacological properties of GABA A and GABA receptors since the topic was last reviewed in 1996. Particular B emphasis is placed on describing the assembly, structure, and function of GABA B sites, the first heterodimeric G protein-coupled receptors identified in vivo. In addition, there are reports dealing with the subunit composition, trafficking, and pharmacological selectivity of GABA receptors. Aside from providing A insights into the fundamental properties of ligand-gated ion channels and second messenger systems, the findings detailed in this work point the way for developing novel therapeutics capable of more selectively manipulating these transmitter sites.